Field study of a retaining wall constructed with clay-filled soilbags. Issue 1 (February 2019) - Liu, Sihong; Fan, Kewei; Xu, Siyuan
Abstract: This paper presents a field study of constructing retaining walls using soilbags that are formed by filling the excavated clayey soils into woven bags (geosynthetics). The strength and deformation of the soilbags filled with clayey soils were studied via laboratory tests. A 100 m testing retaining wall was constructed with soilbags in a waterway project. The lateral deformation, the lateral pressures and the surface settlements of the testing retaining wall were monitored during construction and after 7 months operation. The results show that the soilbags can increase the strength of clayey soils. After 7 months of the completion, the lateral deformation and the surface settlement of the testing retaining wall tend to be stable with the maximum values of 29.4 cm and 19.2 cm, respectively. The lateral earth pressure on the front retaining structure could be positively reduced owing to the interlayer's friction of soilbags. Compared to the conventional gravity concrete retaining wall, about 38% construction cost was saved in the 100 m testing retaining wall.